Variation and change in English /r/ among Tamil Indian Singaporeans. Issue 4 (11th January 2019) - Starr, Rebecca Lurie; Balasubramaniam, Brinda
Abstract: Singapore's multiethnic population has historically been found to differ in their use of a range of English features. As English continues to eclipse the country's other languages, it gains potential as a site for the performance of ethnic identity. At the same time, English‐dominant Singaporeans may be less likely to use features perceived as resulting from non‐native transfer. Integration policies and transnational migration have also arguably reduced the salience of ethnicity in the local sociolinguistic landscape. This study investigates a feature linked to Indian identity, tapped and trilled prevocalic /r/, in the speech of 30 Tamil Singaporeans. A significant change in apparent time is observed, with younger speakers using almost entirely approximant /r/. Variation in /r/ also correlates with home language, cultural context, and phonological environment. We argue that, while non‐approximant /r/ is becoming rarer among Tamil Singaporeans, it continues to serve as a means of indexing Indianness.